(untitled) (Majalah Kedokteran Bandung, 2013)
Peran propolis lebah sebagai terapi adjuvan pada pengelolaan sepsis telah dievaluasi. Penelitian ini bertujuan untuk mempelajari efek perlindungan propolis pada sepsis akibat inokulasi cecal, derajat inflamasi intestinal, dan kadar malondialdehid (MDA) serum. Penelitian dilakukan di Laboratorium Histologi dan Biomedik, Fakultas Kedokteran, Universitas Sebelas Maret, Surakarta, selama periode April–September 2011. Empat puluh tikus Rattus norvegicus L jantan dibagi menjadi lima kelompok: kontrol, sepsis, sepsis+antibiotik, sepsis+propolis, dan sepsis+antibiotik+propolis. Pada hari kedelapan, semua hewan coba dikorbankan untuk diukur konsentrasi MDA serum dan perubahan histopatologi di intestinal. Uji konsentrasi MDA serum menggunakan analysis of variance (ANOVA), sedangkan derajat inflamasi intestinal dengan Uji Kruskall-Wallis, dan untuk menentukan perbedaan kemaknaan digunakan p<0,05. Kadar MDA serum masing-masing kelompok: kontrol 0,27±0,07 Î¼mol/L; sepsis 0,39±0,05 Î¼mol/L; sepsis+antibiotik 0,15±0,03 Î¼mol/L; sepsis+ propolis 0,09±0,05 Î¼mol/L; dan sepsis+antibiotik+propolis 0,21±0,11 Î¼mol/L. Derajat inflamasi intestinal menunjukkan kelompok kontrol derajat 0–3; sepsis derajat 3–4; sepsis+antibiotik derajat 1–3; sepsis+propolis 1–3; dan sepsis+antibiotik+propolis derajat 0–2. Simpulan, ekstrak etanol propolis menurunkan derajat inflamasi intestinal dan kadar MDA serum pada hewan coba model sepsis. [MKB. 2013;45(3):161–6] Ethanol extract of Propolis Reduces the Level of Inflammation and Serum Malondialdehyde in Sepsis Rats Model The role of bee propolis as a adjuvant therapy in the management of sepsis was evaluated. The aim of the study was to investigate the protective effect of propolis against cecal inoculum induced sepsis, the level of intestinal inflammation, and serum malondialdehyde (MDA) concentrations. The study was conducted at School of Medicine, Sebelas Maret University, Surakarta, in April to September 2011. Forty male Rattus norvegicus L rats were divided into five groups: control, sepsis, sepsis+antibiotic, sepsis+propolis and propolis+antibiotic+sepsis groups. On the eighth day, all experimental animals were sacrificed. Serum concentrations of MDA were evaluated. In addition, the histopathological changes in intestinal were assessed. Kruskall-Wallis test with Mann-Whitney analysis were used to determine significant differences. Results were expressed as mean±standard error of the mean, and value of p<0.05 was considered statistically significant. Malondialdehyde serum means levels were control group 0.27±0.07 Î¼mol/L, sepsis 0.39±0.05 Î¼mol/L, sepsis+antibiotic 0.15±0.03 Î¼mol/L, sepsis+ propolis 0.09±0.05 Î¼mol/L, and sepsis+antibiotic+propolis 0.21±0.11 Î¼mol/L respectively. The levels of intestinal inflammation were control groups 0 to 3, sepsis 3 to 4, sepsis+antibiotic 1 to 3, sepsis+propolis 1 to 3, and sepsis+antibiotic+propolis 0 to 2, respectively. In conclusions, ethanol extract of propolis reduces the levels of intestinal inflammation and serum MDA in sepsis animal models. [MKB. 2013;45(3):161–6] DOI: http://dx.doi.org/10.15395/mkb.v45n3.146